A comparison of optically measured daytime OH temperatures over the tropics during solar maximum and minimum periods - Vineeth, C.; Pant, T. K.; Gurubaran, S.; Hossain, M. M.; Sridharan, R. (My University, 2010)
This paper deals with the variability of optically measured daytime OH temperatures during two different solar activity epochs, over Trivandrum (8.5◦N, 76.5◦E), a tropical station in India. The data used for the present study span the period of February–March, during the solar maximum year of 2001 and solar minimum year of 2005. The mean daytime temperature (180±5 K) during the 2001 study period was found to be lower than the mean temperature (195±9 K) of the 2005 study period by ∼15 K. However, apart from this noticeable shift in mean temperature level, the variabilities in the temperature of both years were strikingly similar. Moreover, the wave periodicities present during these periods were also quite similar. Possible reasons for these observations were investigated in the context of the various forcings that control the energetics of the equatorial mesopause region. The observations presented in this study are unique and reveal a number of newer aspects of the energetics of the tropical mesopause.
Keywords: Waves and tides; Mesopause temperature; Hydroxyl airglow; OH temperature; Trivandrum